HUMAS PENDIDIKAN SEBAGAI MEDIA PENINGKATKAN KUALITAS PENDIDIKAN - Mustafa, Wachid (Jurnal Inovasi Pendidikan, 2010)
The program of developing and improving education quality will run smoothly if all communities participate actively. Here, the existence of public relations becomes the main point. If the activities of public relations can be done properly, there will be a good corporation between an education institution and society. Public relation takes a role as an institution which binds society's participation at any activity of improving education quality. In other words, public relation has a function as a means of channel for the society to convey their participation in improving education quality. It is not easy to take a part in developing education for the society; the existence of public relation will overcome it. Public relation in educational institution can be said as a series of activities in order to create harmony with society or other institutions. A qualified education, based on the process point of view, is teaching learning process in which the students experience the qualified learning and it is supported by qualified human resources, sufficient fund, and sophisticated equipments. Public relation helps improve the qualities of education in order to go with the development of the current curriculum through progressing the skills of education staff and management.